Study of Anthropometric Measurements of the Anterior Ethmoidal Artery using Three-dimensional Scanning on 300 Patients - Bortoli, Vinicius Tomadon; Martins, Rafael Ferri; Negri, Krystal Calmeto (International Archives of Otorhinolaryngology, 2017)
Introduction The anterior ethmoidal artery (AEA) is one of the main arteries that supply both the nasal mucosa and the ethmoid sinuses. The AEA shows variability regarding its distance from adjacent structures. Several studies have developed techniques to identify the AEA.Objective This study aimed to compare the measurements from the AEA to the ethmoid bulla and to the frontal beak by using computed tomography of the face, while identifying their intraindividual and interindividual variations. Methods We analyzed 300 CT scans of the face performed at the CT scan Center at Hospital. The average age of subjects was 36 ± 15.1 years (range 4–84).Results We found that the average distance from the AEA to the ethmoid bulla was 17.2 ± 1.8 mm and the distance from the AEA to the frontal beak was 15.1 ± 2.2 mm. Regarding the average distance from the AEA to the frontal beak (AEA-frontal beak), there was a difference between the right and left sides, with the former being 0.4 mm higher on average than the latter. Among the age groups, there was a significant difference of distances between the AEA and the ethmoid bulla (AEA-ethmoid bulla), which were shorter in the ≤ 12 years group. There was a positive and significant correlation between both measurements analyzed, with low values (high) of AEA-ethmoid bulla distance corresponding to low values (high) of AEA-frontal beak distance.Conclusion The measurements obtained adds anatomical knowledge that can serve as a parameter in frontal and ethmoid sinus surgery.
Keywords: ethmoid sinus; anatomy; cone-beam; computed tomography